Anisotropic liquid metal–elastomer composites. Issue 33 (31st July 2019) - Zhu, Lifei; Chen, Yuzhen; Shang, Wenhui; Handschuh-Wang, Stephan; Zhou, Xiaohu; Gan, Tiansheng; Wu, Qixing; Liu, Yizhen; Zhou, Xuechang
Abstract : A reliable and straightforward sedimentation method was developed for the fabrication of liquid metal–elastomer composites with electric, heat transport, and mechanical anisotropy. Abstract : Anisotropic liquid metal (LM)–elastomer composites were fabricated by employing a sedimentation technique. The composite exhibits a remarkable electric anisotropy, heat transport anisotropy and mechanical anisotropy while being frozen. This composite can also be a shape morphing material to develop reconfigurable electronic circuits. This study opens up a powerful strategy for the design of LM–elastomer composites in responsive actuation, thermal regulation, and reconfigurable electronics.